Altruistic Observational Learning - Christoph March; Anthony Ziegelmeyer (Center for Economic Studies and ifo Institute (CESifo), 2016)
We report two information cascade game experiments that directly test the impact of altruism on observational learning. Participants interact in two parallel sequences, the observed and the unobserved sequence. Only the actions of the observed entail informational benefits to subsequent participants. We find that observed contradict their private information significantly less often than unobserved when the monetary incentives to herd are moderately weak. Long laboratory cascades accumulate substantial public information which increases the earnings of participants. In Experiment 2, participants have better opportunities to learn about the strategies played by observed which amplifies the impact of altruism on observational learning.
Keywords: D64; D82; D83; 330; social learning; informational herding; altruistic behavior